Mid-Long Term Results in the Arthroscopic Selective Capsular Release and Manipulation Treatment of Frozen Shoulder - Celik, Haluk (Orthop J Sports Med, 2014)
OBJECTIVES: Our aim was to present mid-long term functional outcomes of patients who underwent arthroscopic selective capsular release and manipulation for frozen shoulder refractory to conservative treatment. METHODS: Between 2006 and 2012, 32 patients presented to our clinic with the diagnosis of frozen shoulder. 24 shoulders of 22 patients treated with arthroscopic selective capsular release and manipulation were included in the study. Functional results were analyzed with Constant shoulder score. The mean follow-up was 4.3 years (range 1-7 years). RESULTS: We detected an average increase in passive range of motion in flexion 72°, abduction 90°, abduction-internal rotation 33°, and abduction-external rotation 38°, adduction-external rotation at 37° compared to the preoperative status. Constant shoulder score increased by an average of 44 points after surgery. Eighteen (82%) patients were satisfied with the operation. Three of four patients whose symptoms persisted had resistant diabetes mellitus. CONCLUSION: Frozen shoulder is one of the most well-known causes of shoulder pain and disability. Although surgery has a good rate of success it does not help in all cases. Unsatisfactory results may be experienced in patients who have diabetes mellitus as a confounding factor.